Potential role of potassium and chloride channels in regulation of silymarin‐induced apoptosis in Candida albicans. Issue 3 (22nd January 2018) - Lee, Wonjong; Lee, Dong Gun
Abstract: Silymarin, which is derived from the seeds of Silybum marianum, has been widely used to prevent and treat liver diseases. In our previous study, we reported that at concentrations above the minimal inhibitory concentration (MIC), silymarin exhibited antifungal activity against Candida albicans by targeting its plasma membrane. However, the antifungal mechanism at concentration below the MIC remains unknown. Therefore, we aimed to determine the underlying mechanism of antifungal effects of silymarin at concentration below the MIC. To evaluate the inhibitory effects on the ion channels, C . albicans cells were separately pretreated with potassium and chloride channel blockers. The antifungal activity of silymarin at sub‐MIC was affected by the ion channel blockers. Potassium channel blockade inhibited the antifungal effects, whereas chloride channel blockade slightly enhanced these effects. Subsequently, we found that silymarin induced disturbances in calcium homeostasis via the cytosolic and mitochondrial accumulation of calcium. Furthermore, apoptotic responses, such as phosphatidylserine exposure, loss of mitochondrial membrane potential (MMP), DNA damage, and caspase activation were induced in response to silymarin treatment. The increases in intracellular calcium level and pro‐apoptotic changes were prevented when potassium ion channels were blocked. In contrast, these changes were enhanced upon chloride channels blockade; however, this did not affect the intracellular calcium levels and MMP loss. Thus, we showed that silymarin treatment at concentration below the MIC induced apoptosis in C . albicans ; additionally, ion channels contributed these effects. © 2018 IUBMB Life, 70(3):197–206, 2018